Quelques exemples d’analyse des corpus en vue de la traduction - Vetulani, Grażyna (Wydawnictwo Naukowe UAM, 2000)
Intensive works by (first) computer scientists and (then) linguists in order to obtain Automatic Translation Systems started already in the late 40-ties. Since that time many things have changed in the field of tools and methodologies like for example creation of basic electronic resources as corpora and dictionaries or the lexicon-grammar framework. This paper presents some language engineering tools recently developed (with participation of the Author) for Polish and claims their interest for the Translation Community.
Some examples of corpus analysis on the way of translation